Study on Jackals Egesta Inhabiting District Karak, Khyber Pakhtunkhwa in Perspective of Their Future Abundance - Mansoor Ullah; Alam, Asfandyar; Ahmad, Ijaz; Aleem Ullah; Hafiz Anwar Ullah; Mohammad Salim; Ali, Wajahat; Khan, Zafar Ali (Indus Journal of Bioscience Research, 2025)
The goal of the current study was to determine the diet ecology of the population of jackal’s residing in various areas of the district Karak. It was carried out at the GPGC Karak Zoology Department. Total 96 scats samples were gathered from various locations. The purpose of this study was to learn more about the district Karak Asiatic jackal population's dietary preferences and projected abundance. Each and every sample from the scats was examined in a lab. The current study's findings suggested that the average percent volume composition (N=96) of scats samples from each of the three sites (Tehsils) in the district of Karak showed that this sample constitutes 48%plant matters, 42.22%animal matters, and 4.12% soil, while average anthropogenic materials recovered from all scats samples were 5.7% by volume. Particularly, the plant materials include seeds, grass, tiny leaves and stems, wheat (Triticumaestivum), Bair (Zizyphus spp.), Bajra (Pennisetumglaucum), zheera (Cuminumcyaminum), chana (Cicerarietinum), orange (Citrus sinensis), melon (Cucumismelo), water melon (Citruluslanatus).  Similar to the animal matter, which consists of bones, scat analysis also revealed the presence of house rats (Rattusrattus), dogs (Canisfamiliaris), rabbits (Oryctolaguscuniculus), goats (Capra hircus), sheep (Ovisaries), cows (Bos Taurus), reptiles and some invertebrates. The soil and anthropogenic elements, in addition to plant and animal material, altered the food preferences of Asiatic jackals.